Quick and simultaneous determination of caffeine and taurine in beverages using UPLC-ESI-MS - Alam, Mohd Aftab; Al-Arifi, Rayan Saud; Al-Qarni, Abdulaziz Abdullah; Al-Dosseri, Abdullah Shaya; Al-Jenoobi, Fahad Ibrahim (European Journal of Chemistry, 2021)
A rapid UPLC-ESI-MS method was developed for simultaneous determination of caffeine and taurine in beverages (energy drinks and soft drinks). The molecular ions of caffeine and taurine were identified in single ion recording mode at m/z 194.98 and 125.86, respectively. The mass spectrometer parameters were optimized as: capillary voltage 3.0 kV, cone voltage 35 V, extractor 3 V, RF Lens 0.1 V, source temperature 150 °C, desolvation temperature 350 °C, nitrogen 600 L/h, LMR1 7.9, HMR1 15.2, IE1 0.30. The mobile phase comprising methanol (0.1% formic acid) (A) and water (5 mM ammonium acetate) (B) was used in gradient mode. The mobile phase components A and B were pumped in 80:20 (v:v) ratio from 0-0.44 min, and then 100% of component A was pumped between 0.45-0.68 min, and at 0.69 min the composition was returned to 80:20 (v:v) ratio of A and B till 2.0 min. Caffeine and taurine were eluted at 0.46 and 0.43 min, respectively. The samples of energy drinks and soft drinks were diluted in a solvent system comprising methanol and water in 80:20 (v:v) ratio. Our investigations showed that soft drinks SD1 and SD2 have 88.8±4.2% and 110.7±3.6% (w:w) caffeine of their labeled claim. The caffeine content in energy drink brands ED1, ED2, ED3, and ED4 was 76.9±2.5, 65.6±3.4, 88.1±12.6, and 89.1±2.8% (w:w) of labeled claims, respectively. While taurine content in ED1, ED2, ED3, and ED4 was 86.5±8.4, 81.3±27.5, 101.9±4.8, and 97.1±0.3% (w:w) of labeled claim, respectively.